LEGAL PROTECTION OF CHILDREN AS PEOPLE OF NARCOTIC ABUSE - Ningtias, Ayu Dian; Fahrudin, Mukhlis; Maghfiroh, Lailatul (Jurnal Independent, 2022)
ABSTRACT Based on Article 67 of Law Number 35 of 2014 concerning Child Protection, it is explained that special protection is for Children who are victims of abuse of narcotics, alcohol, psychotropic substances, and other addictive substances as referred to in Article 59 paragraph (2) letter e and Children involved in the production and its distribution are carried out through surveillance, prevention, treatment, and rehabilitation efforts. concerning child protection in Article 1 number (2) it states "Child protection is all activities to guarantee and protect children and their rights so that they can live, grow, and develop. develop, and participate optimally in accordance with human dignity , and receive protection from violence and discrimination”.